Key biotic stresses affecting tuber crops - Makeshkumar, T; Kumar, H Kesava; Arutselvan, R (Indian Horticulture, 2025)
Across the humid tropics, cassava, sweet potato, yams, taro, and elephant foot yam face intense biotic pressure. Insects, mites, weevils, fungi, viruses, nematodes, weeds, rodents and wild boar cause 20-90% yield losses, degrade tuber quality, and raise production costs. Vegetative propagation and vectors (whiteflies, aphids) hasten disease spread. Together with abiotic stresses, these factors are elevating the risk of emerging diseases, notably cassava stem/root and elephant foot yam leaf-pseudostem rot. An integrated IPM-IDM approach involving the use of clean seed systems, resistant/tolerant varieties, early surveillance, good drainage, community coordination, and rigorous post-harvest hygiene is central to safeguarding yield and income.